Supercritical water gasification of high-salinity oily wastewater: study on inorganic salt deposition behavior and mechanisms - Siqi Rong; Hanbing Jia; Kun Jiang; Libo Lu; Zhiyong Peng; Jialing Xu; Hui Jin; Liejin Guo (Fuel, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Continuous coagulant and alkali dosing enhanced organic separation from hypersaline wastewater in synchronous ozonation coagulation process - Yuhan Yang; Mengwen Liu; Rong Liu; Yiqiao Shi; Yadong Wang; Yukai Zong; Zimin Lu; Xu Lu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Water Research, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Enhancing robustness in small-sample prediction of oily sludge supercritical water gasification: A generative adversarial network data augmented hybrid machine learning strategy - Jianghua Tian; Jiale Hou; Lingyu Shi; Zhiyong Peng; Lei Yi; Le Wang; Siqi Rong; Jialing Xu; Libo Lu; Hui Jin (Journal of Environmental Chemical Engineering, 2026)

Profiling hydrophobic organic pollutants in serum from vulnerable populations in Dalian, China - Yubing Dai; Ningbo Geng; Dongying Zheng; Jing Jin; Xianbo Lu; Rong Cao; Haijun Zhang; Jiping Chen (Environmental Pollution, 2026)

Synergistic antifouling and organic removal using Fe/N co-doped biochar-modified ceramic membranes via in situ peroxymonosulfate activation - Rong Liu; Ye Zhu; Peng Ren; Jinge Fan; Yadong Wang; Mengwen Liu; Yabo Shang; Lu Xu; Xue Bai; Xuan Shi; Xin Jin; Pengkang Jin (Chemical Engineering Journal, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

(±)-Involucrasin D, a pair of enantiomeric bisflavonoid from the roots of Shuteria involucrata and its anti-inflammatory activity - Xiaoying Zhou; Qiong Jin; Bingruo Zhang; Lisha Wei; Lue Bao; Xiaoyun Jiang; Rong Duan; Lu Liu; Zhuya Yang (Natural Product Research, 2025)

Isolation and genomic characterization of multi-drug resistant Morganella morganii strain from Chinese Soft-Shell Turtle Pelodiscus sinensis - Rong-Hua Wang; Meng-Lu Yan; Qing Tan; Jin-Long Wang; Yu-Shuang Luo; Zhong-Yuan Chen (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Synergistic enhancement of flame retardancy, mechanical properties, dimensional stability, and mold resistance in bamboo via silica mineralization and hydrophobic treatment - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2025)

Assessment of Geostationary Satellite Cloud Effective Radius over East China with In Situ Aircraft Measurements - Qiuli Zhang; Chao Liu; Rong Zhang; Jing Yang; Junxia Li; Bo Li; Feng Lu; Yan Yin; Hongchun Jin (Journal of Meteorological Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Ternary Ni:Fe- activated inert Cu-based electrocatalyst as efficient bifunctional electrocatalysts for water splitting - Shi-Yu Lu; Chunjie Wu; Tingting Hu; Ling Wang; Wenzhao Dou; Jun Zhang; Rong Wang; Yin Liu; Qian Yang; Zhigang Zou; Meng Jin (Chemical Engineering Journal, 2025)

High/Low-Index Faceted PdNi Alloy Nanocrystals as Highly Active and Stable Electrocatalyst for Oxygen Reduction - Jun Zhang; Xinlan Xu; Lanyu Luo; Tiantian Peng; Boyu Liu; Lingying Jiang; Meng Jin; Rong Wang; Huan Yi; Weimin Wu; Shi-Yu Lu (Chemical Engineering Journal, 2025)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Strong electronic interaction in chromium-molybdenum dual incorporated few-layer cobalt sulfide nanosheets with lattice distortion for efficient bifunctional water splitting - Shi-Yu Lu; Wenzhao Dou; Chunjie Wu; Jun Zhang; Ling Wang; Tingting Hu; Rong Wang; Yin Liu; Qian Yang; Meng Jin (Fuel, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Effects of low-temperature stress on serum biochemical indicators, intestinal microbiome, and transcriptome of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Aquaculture International, 2024)

External redox couple enhanced anammox sludge activity at low temperature: Insight into intracellular resource synthesis - Rong-Rong Chang; Wei Yao; Jin-Luo Pang; Kai-Yue Dong; Yao-Yao Lu; Bao-Cheng Huang; Ren-Cun Jin (Water Research, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

A literature review on phosphate removal from wastewater by lanthanum-based adsorbents: From mechanisms to applications - Yao-Yao Lu; Hao Wang; Rong-Rong Chang; Wen-Bing Li; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

A green and eco-friendly method to enhance Bamboo flame resistance via calcium alginate assisted in-situ mineralization of hydroxyapatite - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Ying He; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2024)

Reactant enrichment in yolk-shell structured Pd/TiN nanoreactors for boosting electrocatalytic hydrodechlorination performance - Jun Zhang; Chunyuan Wang; Shiyu Lu; Shuyue Liu; Pingjuan Liang; Huan Yi; Mengjie Li; Meng Jin; Rong Wang; Guangming Jiang (Chemical Engineering Journal, 2024)

Uptake and transport of micro/nanoplastics in terrestrial plants: Detection, mechanisms, and influencing factors - Zhefu Yu; Xiaolu Xu; Liang Guo; Rong Jin; Yin Lu (Science of The Total Environment, 2024)

Ultrastable Dual-Matrix meditated CsPbBr3 composites with enhanced photoluminescence quantum yield and robust circular polarization luminescence - Pengfei Zhang; Rong Lu; Yang Chen; Huihui Wang; Mei Zhao; Lijie Zhang; Huile Jin; Shun Wang; Yihuang Chen; Shuang Pan (Chemical Engineering Journal, 2024)

Direct and indirect photodegradation of bisphenol A in the presence of natural water components - Yao Han; Lijun Li; Lu Jin; Rong Zhou; Yayu Li; Weiwen Jing (Environmental Geochemistry and Health, 2024)

Rapid and sensitive Cas13a/Cas12a-based one-pot dual-target strategy to detect monkeypox virus and its co-infected viruses - Xiao Wang; Qiao Rao; Zhengrong Lu; Xiaobao Deng; Rong Shen; Rui Wang; Weiyi Dong; Xianhua Qi; Zhen Jin; Youzhi Tang; Dan Du (Science Bulletin, 2023)

Mechanism of E2F1 in the proliferation, migration, and invasion of endometrial carcinoma cells via the regulation of BMI1 transcription - Yanyang Lu; Ying Wei; Xiaoqin Shen; Yixi Tong; Jin Lu; Yahui Zhang; Yun Ma; Rong Zhang (Genes & Genomics, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Characterization of airborne microplastics at different workplaces of the poly(ethylene:propylene:diene) (EPDM) rubber industry - Xiaoni Sun; Rong Song; Jintao Liu; Shuangshuang Yan; Yuxuan Li; Xiaoyu Jin; Yunfeng Liang; Yudong Wu; Lu Mei; Rubing Pan; Weizhuo Yi; Jian Song; et al. (Environmental Science and Pollution Research, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Neoproterozoic tungsten mineralization: Geology, chronology, and genesis of the Huashandong W deposit in northwestern Jiangxi, South China - Xu-Dong Huang; Di Huang; Jian-Jun Lu; Rong-Qing Zhang; Dong-Sheng Ma; Yao-Hui Jiang; Hao-Wen Chen; Jin-Xian Liu (Mineralium Deposita, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Frontiers in Marine Science, 2023)
Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano ( Trachinotus ovatus ) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The results showed that: (1) the swelling degree of the muscle layer deepened and was congested with a longer low-temperature stress period. The folds were sparse, from slight swelling to shedding and deformation. The intestinal mucosa was necrotic and had vacuoles, and the number gradually increased. Serious erosion of the villi occurred. (2) The specific activities of digestive enzymes showed a downward trend. (3) The intestinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and glutathione peroxidase (GSH-Px) activity showed an upward trend. The intestinal catalase (CAT) activity showed a downward trend. (4) Compared with the control group, there were 28 metabolites in the cold group showing significant differences, among which Z, 11Z, 14Z-eicosatrienoic acid, stearic acid, and adrenic acid showed an upward trend. In contrast, spermidine and uracil showed a downward trend. Among the enriched metabolic pathways, the main differential pathways were unsaturated fatty acid biosynthesis, fatty acid biosynthesis, linoleic acid metabolism, pyrimidine metabolism, and β-alanine metabolism. According to metabolomic analysis, under low-temperature stress, the fish body improved the synthesis of unsaturated fatty acids and saturated fatty acids to adapt to a low-temperature environment and consumed spermidine to improve its immune ability to clear the peroxide generated by the synthesis of unsaturated fatty acids in the body so that the cells were protected from oxidative damage. After 14 days, low-temperature stress affected metabolites and enzyme activity indices in juvenile golden pompano. Low-temperature stress causes changes in intestinal antioxidants and digestive enzymes and damage intestinal tissues. As a result of this exploration of how low temperatures affect the juvenile golden pompano, the foundation is laid for future studies, such as the molecular mechanisms of low-temperature adaptation in fish species.

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Multicopper oxidases GbAO and GbSKS are involved in the Verticillium dahliae resistance in Gossypium barbadense - Fei Wang; Tianxin Lu; Liping Zhu; Aiping Cao; Shuangquan Xie; Xifeng Chen; Haitao Shen; Quanliang Xie; Rong Li; Jianbo Zhu; Xiang Jin; Hongbin Li (Journal of Plant Physiology, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Environmental Quality and Ecological Risk Assessment of Heavy Metals in the Zhuhai Coast, China - Jin Wu; Shaowei Rong; Miaowei Wang; Rong Lu; Jingchao Liu (Frontiers in Marine Science, 2022)
The rapid urbanization and industrialization in the coastal Zhuhai have resulted in severe heavy metal contamination. Heavy metals are extensively used as indicators of coastal contamination, but the comparability among different geographic environments needs to be further explored and scrutinized. In this study, heavy metals (i.e., As, Zn, Cd, Cr, Hg, Cu, and Pb) in surface seawater (20 sites), sediments (10 sites), and organisms (13 sites, shellfish, algae, fish, and crustaceans) were analyzed to assess the distribution, enrichment, and ecological risk in the coastal regions of Zhuhai (2017 and 2018). The results showed that Cu, Zn, and Pb exceeded the standards of seawater, indicating the presence of anthropogenic pollution. Meanwhile, the ecological risk results showed that Cd and Cu indicated moderately high environmental risks. The quantity and quality of heavy metals in organisms showed different trends in the sea, which affected marine organisms in the northeastern area. The main factors contributing to the ecological risk of these two heavy metals are the emissions from chemical companies. Therefore, preserving the high biological diversity in this area is important to ensure the health and productivity of the seawater ecosystem in the coastal area. These results may play a key role in promoting decision makers to manage the sustainability of the Zhuhai coast.

Four new triterpene glucosides from Salacia cochinchinensis Lour - Lu Gao; Li-Kun Duan; Jin-E Feng; Yun-Tao Jiang; Jun Gao; Jun-Ting Fan; Rong Dai; Zhi-Yong Jiang (Natural Product Research, 2022)

Control of chronic obstructive pulmonary disease in urban populations: findings from a cross-sectional prevalence survey in Shenzhen, China - Le-Cai Ji; Jin-Feng Yin; Chun-Rong Lu; Hong-Yun Guan; Wei-Guo Tan; Ling-Wei Wang; Qi Jiang (Environmental Science and Pollution Research, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Establishment and optimization of a high-throughput mimic perfusion model in ambr® 15 - Lu Jin; Zhen-Shou Wang; Yun Cao; Rui-Qiang Sun; Hang Zhou; Rong-Yue Cao (Biotechnology Letters, 2021)

Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Anti-angiogenic Effects of Bumetanide Revealed by DCE-MRI with a Biodegradable Macromolecular Contrast Agent in a Colon Cancer Model - Anthony S. Malamas; Erlei Jin; Qi Zhang; John Haaga; Zheng-Rong Lu (Pharmaceutical Research, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

Dynamic patterns of histone H3 lysine 4 methyltransferases and demethylases during mouse preimplantation development - Gen-Bao Shao; Jun-Chao Chen; Liu-Ping Zhang; Pan Huang; Hong-Yan Lu; Jie Jin; Ai-Hua Gong; Jian-Rong Sang (In Vitro Cellular & Developmental Biology - Animal, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Differentiation and distribution of indica and japonica rice varieties along the altitude gradients in Yunnan Province of China as revealed by InDel molecular markers - Zhiyuan Xiong; Shujie Zhang; Yunyue Wang; Brian V. Ford-Lloyd; Min Tu; Xin Jin; Yue Wu; Huanxin Yan; Xiao Yang; Ping Liu; Bao-Rong Lu (Genetic Resources and Crop Evolution, 2010)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Involvement of MAPK/ERK kinase-ERK pathway in exogenous bFGF-induced Egr-1 binding activity enhancement in anoxia-reoxygenation injured astrocytes - Ying Liu; Jin-Biao Lu; Qi Chen; Zhu-Rong Ye (Neuroscience Bulletin, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Genetic spatial clustering: significant implications for conservation of wild soybean (Glycine soja: Fabaceae) - Yan Jin; Tianhua He; Bao-Rong Lu (Genetica, 2006)

Mapping of leaf and neck blast resistance genes with resistance gene analog, RAPD and RFLP in rice - Jie-Yun Zhuang; Wen-Bin Ma; Jian-Li Wu; Rong-Yao Chai; Jun Lu; Ye-Yang Fan; Min-Zhong Jin; Hei Leung; Kang-Le Zheng (Euphytica, 2002)